The Formulation and Determination of Total Flavonoid Content of Gel Preparation Akalifa Leaf Extract (Acalypha wilkesiana Muell.Arg) - Precilia Renanda Sherly Sherly; Dhina Ayu Susanti (Indonesian Pharmacopeia Journal, 2025)
Skin damage is mainly caused by ultraviolet radiation, which necessitates the use of sunscreen. Sunscreen is a skincare product that protects the skin from sun exposure. Plants that can be used as sunscreen include the leaves of akalifa (Acalypha wilkesiana Muell. Arg). Alkaloids, flavonoids, phenols, tannins, and saponins are all found in akalifa leaves. Phenolic compounds, particularly flavonoids, have potential as sunscreen. To formulate a gel preparation and conduct testing of the total flavonoid content of the gel formulation from acalypha leaf extract (Acalypha wilkesiana Muell. Arg.). This study uses a laboratory experimental research design by extracting akalifa leaves using the UAE (Ultrasonic Assisted Extraction) method with 96% ethanol as the solvent. The gel preparation of the akalifa leaf extract is formulated at concentrations of 6%, 8%, and 10%. The formula involves determining the total flavonoid content of the gel preparation using UV-Vis spectrophotometry at a wavelength of 430 nm. The determination of total flavonoid content in formulation 1 is 1,888 mg QE/gram, in formulation 2 is 2 mg QE/gram, and in formulation 3 is 2,102 mg QE/gram. In the three formulations of concentrations 6%, 8%, and 10% formulation 3 has the highest flavonoid content.